1-Nitro-4-(1-propyn-1-yl)benzene - Campos Fernández, Cristian Saúl (2019)
The title compound, C9H7NO2, was prepared by alkynylation of 4-iodonitrobenzene with 1,3-dilithiopropyne in the presence of 1 equivalent of CuI and catalytic amounts of Pd(PPh3)2Cl2. The complete molecule is generated by crystallographic twofold symmetry with the C—N and C—C[triple bond]C—C units lying on the rotation axis. No directional interactions beyond normal van der Waals contacts could be identified in the packing.